Amos in der bildenden Kunst, (Teil 1), Hirte, Gelehrter, Sozialkritiker, Unheilsbote, Heilsbote, Christusbote ... - Koenen, Klaus (Die Bibel in der Kunst, 2020)
This article presents an overview of depictions of Amos in visual art. In line with Amos 7.14 the prophet is depicted as shepherd, sometimes in ways that remind us of depictions of Jesus as good shepherd. Other images show him with a scroll or books, suggestive of his role as author, teacher or wise man. However, there is no definitive way to depict him in a manner that distinguishes him from other prophets. Consequently, it is only possible to recognize him from his context, from the phylacteries that give his name, a verse of his book or a summary of his message. In the Middle Ages the Old Testament was interpreted typologically as referring to Christ. Images of Amos depict him as a prophet who predicts the birth of Jesus (9.13; 4.13?), the cleansing of the temple (5.10; 6.12), elements of the passion narratives (5.7; 8.3-4; 8.9) and - very often - the Ascension (9.6), the Last Judgement and Pentecost. In the sixteenth-century Reformation, when the Bible was interpreted more literally, Amos’s message of doom came to the fore and, in visual art, is frequently represented in popular woodcarvings which were printed in the Lutheran Bible and the Zürcher Bible. His accusatory message dominated the reception history of Amos until more recent times. However, in light of 9.11ff. his message has also been consistently regarded as a message of salvation. The second part of this article will appear in The Bible in the Arts 2021.